Rationale and design of the Self-TI Study protocol: a cross-sectional human papillomavirus self-testing pilot study among transgender adults in England - Alison May Berner; Chloe M Orkin; Sarah S Jackson; Stewart O’Callaghan; Elanore Ward; Megan A Clarke (BMJ Open)
Introduction Persistent infection with high-risk human papillomavirus (HPV) is the causal agent of several cancers including cervical, anal and oropharyngeal cancer. Transgender men and transmasculine non-binary (TMNB) people with a cervix are much less likely to undergo cervical cancer screening than cisgender women. Transgender women and transfeminine non-binary (TWNB) people assigned male at birth may be at increased risk of HPV. Both TMNB and TWNB people face many barriers to HPV testing including medical mistrust due to stigma and discrimination.Methods and analysis The Self-TI Study (Self-TI) is a pilot study designed to measure acceptability and feasibility of HPV self-testing among transgender and non-binary people in England. TMNB people aged 25–65 years, with at least 1 year of testosterone, and TWNB people, aged 18 years and over, are eligible to participate. Participants self-collect up to four samples: an oral rinse, a first void urine sample, a vaginal swab (if applicable) and an anal swab. TMNB participants are asked to have an additional clinician-collected cervical swab taken following their routine Cervical Screening Programme sample. TWNB people are asked to take a self-collection kit to perform additional self-collection at home and mail the samples back to the clinic. Acceptability is assessed by a self-administered online survey and feasibility is measured as the proportion of samples returned in the clinic and from home.Ethics and dissemination Self-TI received ethical approval from the Research Ethics Committee of Wales 4 and ethical review panel within the Division of Cancer Epidemiology and Genetics at the US National Cancer Institute. Self-TI was coproduced by members of the transgender and non-binary community, who served as authors, collaborators and members of the patient and public involvement (PPI) group. Results of this study will be shared with the community prior to being published in peer-reviewed journals and the PPI group will help to design the results dissemination strategy. The evidence generated from this pilot study could be used to inform a larger, international study of HPV self-testing in the transgender and non-binary community.Trial registration number NCT05883111.